Revolution for education: the beginning of the Peruvian reform in the teaching of engineering through the CDIO initiative - Cáceres Huamán, Víctor Roy (2018)
Currently, the Peruvian State is carrying out an educational reform at all levels of university education. In the case of engineering education, this effort is not accompanied by new proposals for innovation and technology. Given the scarcity of competitive models, the future of this reform will leave aside the extraordinary opportunity to generate competitive engineering professionals. The CDIO Initiative proposes an education that emphasizes the fundamentals, established in the context of Conceiving, Designing, Implementing and Operating products, processes, and systems. It focuses on teaching engineering through the promotion of practical learning of the products and the creation of the system. Students face real engineering problems that require a combination of tangible theoretical and practical solutions. The idea is to expose students to difficult situations that require both multidisciplinary knowledge and social learning. In this present work, a preliminary evaluation is developed in the various initiatives being developed by the School of Industrial Engineering and Systems of the National University of Engineering in the accreditation process for university education, hoping to achieve a new innovative educational engineering model CDIO